Power System Grid Operation Using Synchrophasor Technology - Nuthalapati, Sarma (NDR) (Power Electronics and Power Systems,, 2019)
This book brings together successful stories of deployment of synchrophasor technology in managing the power grid. The authors discuss experiences with large scale deployment of Phasor Measurement Units (PMUs) in power systems across the world, enabling readers to take this technology into control center operations and develop good operational procedures to manage the grid better, with wide area visualization tools using PMU data. · Provides a single-source reference to the practical applications of Synchrophasor technology in operating the power grid; · Includes real case studies from utilities that have deployed the technology; · Offers an international perspective on the use of data obtained from phasor measurement units, in order to manage power grids.